2019
DOI: 10.1017/s0022029919000785
|View full text |Cite
|
Sign up to set email alerts
|

Screening candidate microR-15a- IRAK2 regulatory pairs for predicting the response to Staphylococcus aureus-induced mastitis in dairy cows

Abstract: We established a mastitis model using exogenous infection of the mammary gland of Chinese Holstein cows with Staphylococcus aureus and extracted total RNA from S. aureus-infected and healthy mammary quarters. Differential expression of genes due to mastitis was evaluated using Affymetrix technology and results revealed a total of 1230 differentially expressed mRNAs. A subset of affected genes was verified via Q-PCR and pathway analysis. In addition, Solexa high-throughput sequencing technology was used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The main bacteria causing mastitis in dairy cows are Streptococcus dysgalactiae, Streptococcus uberis, S. agalactiae, S. aureus , and E. coli ( 31 , 32 ); the latter three have been identified and studied by animal models ( 33 35 ). In particular, some studies have used phages to treat a mouse mastitis model caused by S. aureus and E. coli , which have shown therapeutic effects in vivo ( 25 , 36 , 37 ), indicating that the application of phages is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…The main bacteria causing mastitis in dairy cows are Streptococcus dysgalactiae, Streptococcus uberis, S. agalactiae, S. aureus , and E. coli ( 31 , 32 ); the latter three have been identified and studied by animal models ( 33 35 ). In particular, some studies have used phages to treat a mouse mastitis model caused by S. aureus and E. coli , which have shown therapeutic effects in vivo ( 25 , 36 , 37 ), indicating that the application of phages is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-15a, involved in our study in as many as 28 pathways, was described as controlling functions that regulate the inflammation and differentiation of immune cells (Calin et al, 2008;Moon et al, 2014;Chen et al, 2019) as well as mediating the differentiation of adipocytes in goats, thus suggesting also a role in stimulating the synthesis of milk fat (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, their luciferase-reporter assay results indicate that miR-15a significantly inhibited luciferase activity, suggesting that it acted through the 3'-UTR of IRAK2 to suppress reporter-gene expression. Studies have shown that IRAK2 has a significant negative regulatory function and can reduce the mast-cell apoptosis induced by lipopolysaccharide infusion; miR-15a, according to previously obtained data, is involved in multiple functions that regulate the inflammation and differentiation of immune cells [206][207][208].…”
Section: Immunological Role Of Mammary Gland Mirnas and Their Functions In Breast Diseasesmentioning
confidence: 70%
“…Inflammatory response to mastitis [198,199,[201][202][203][204] miR-223 CBLB Mammary alpha T cells stimulation [62] miR-145 FSCN1 Levels of cellular immune cytokines [208] miR-15a IRAK2 Inflammation and differentiation of immune cells [206][207][208] miR26a FGA…”
Section: Immunological Role Of Mammary Gland Mirnas and Their Functions In Breast Diseasesmentioning
confidence: 99%